Detection the Infections with Viral Hepatitis C in Suwayrah / Wasit Governorate/ Iraq - Humam Kasem Hussein (Journal of Global Pharma Technology, 2016)
Background: Hepatitis C virus (HCV) is worldwide distributed virus which may lead to the death, its responsible for 15-20% of acute hepatitis. Then, most of these cases will progress to chronic infection. IL-8 considered as a good indicator of liver disorder such as liver carcinoma, which is one of the main complication of infection with HCV. Objective: This study was carried out to detect infection of HCV and its association with serum level of IL-8 by ELISA kits.  Materials and methods: Blood specimens were collected from suspected persons who visited Suwayrah General Hospital during the period from March 2018 to September 2018. Blood specimens (5 ml) were taken from them under aseptic conditions and left for 10 minutes for spontaneous clotting at room temperature before being centrifuged (6000 rpm) to separate the serum. Serum samples were kept frozen at –20°C for determination of HCV Abs and IL-8 levels. Results: The results showed that, this virus was detected in 14 male (58.3%) and in 10 female (41.7%). Most age period susceptible to HCV was 21-40 years 14 (58.3%). Level of IL-8 in HCV patients was (210±2.422 pg/ml) which significantly high (p<0.05) than healthy persons was (48±3.241 pg/ml).  Conclusions: Absence of prophylactic procedures especially vaccination make HCV highly infectious and fatal disease. Both genders are under attack of HCV infection. Age period of the individuals associated with the resistance to gain this virus. IL-8 is a good indicator to liver disease such as HCV.Keywords: Hepatitis C virus; Hepatic inflammation; Liver cirrhosis; Hepatocellular cancer and IL-8.